Thinking styles influence on the individual\'s readiness for adopting design thinking in organizations - Seii, Willian (2018)
Private sector, government and the academia have been recognizing the value of a \'designerly\' approach to business problems, in the context that the traditional technical-rationality has been insufficient to address issues in the contemporary volatile, uncertain, complex and ambiguous environment. Design Thinking has been growing since Tim Brown, CEO of a prestigious global design agency, started advocating and disseminating this approach in the business environment ten years ago. As more organizations are implementing Design Thinking (DT), this research aims to analyze the relation between individuals\' Readiness for adopting DT in organizations and their thinking styles, namely Rationality and Experientiality. From the literature review, some authors characterize Design Thinking by its focus on human needs, open objectives so creativity can arise, iteratively, reliance on qualitative methods, intuition and experience, - to name some of the characteristics. Accordingly, the initial hypothesis of this research stated that individuals with high Experientiality score would be the ones with higher Readiness to adopt Design Thinking. A quantitative survey was designed based on existing instruments in the academic literature. For assessing the thinking styles, the Rationality-Experientiality Inventory (REI) developed by Pacini & Epstein (1999) was integrally applied; for measuring the individual\'s Readiness for adoption of Design Thinking, the Readiness for Organizational Change Measure (ROCM) developed by Holt, Armenakis, Feild, & Harris (2007b) was partially applied; and to collect the respondents\' understanding on Design Thinking, questions were designed based on the paper published by Glen, Suciu & Baughn (2014). The sample size had 251 valid respondents from the state of Sao Paulo (Brazil), with declared knowledge or experience with Design Thinking. One-way ANOVA was conducted to determine significant differences within the terciles of Rationality, Experientiality and Readiness-for-change and between the thinking styles terciles and the score of Readiness for adopting Design Thinking; Regression Analysis was conducted to determine, among all variables in the research, which are the ones explaining Readiness for adopting Design Thinking. The results pointed out that the group of individuals with high score of Rationality (third tercile) presented higher Readiness for adopting Design Thinking, as well as the third and first terciles of Experientiality. Furthermore, when Rationality and Experientiality scores were analyzed together, both thinking styles did have influence on the individuals\' Readiness for adopting Design Thinking. The understanding of the level of individual\'s thinking styles provides some light on the challenges ahead regarding the acceptance of Design Thinking. Smoother and more efficient change management programs can be designed for educational programs relying on Design Thinking or for departments in organizations implementing Design Thinking. These findings may implicate in further researches in the cognitive field of Design Thinking, as the success of DT adoption in organizations can be influenced by the thinking style profile which is dominant in the selected department or functional area to be implemented.